2014
DOI: 10.1016/j.neuron.2014.08.023
|View full text |Cite|
|
Sign up to set email alerts
|

Bidirectional Modulation of Incubation of Cocaine Craving by Silent Synapse-Based Remodeling of Prefrontal Cortex to Accumbens Projections

Abstract: Summary Glutamatergic projections from the medial prefrontal cortex (mPFC) to nucleus accumbens (NAc) contribute to cocaine relapse. Here we show that silent synapse-based remodeling of the two major mPFC-to-NAc projections differentially regulated the progressive increase in cue-induced cocaine seeking after withdrawal (incubation of cocaine craving). Specifically, cocaine self-administration in rats generated AMPA receptor-silent glutamatergic synapses within both infralimbic (IL) and prelimbic mPFC (PrL) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
391
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(414 citation statements)
references
References 57 publications
20
391
3
Order By: Relevance
“…A minimal stimulation assay (Isaac et al, 1995;Liao et al, 1995;Huang et al, 2009) revealed that silent synapse levels were significantly increased within this projection (Figure 2a-c; t(25) = 2.69, po0.05, saline 21.27 ± 8.08%, cocaine 47.03 ± 5.60%). We also noted that the basal (saline) levels of silent synapses (~20%) appear to be higher in this projection than other NAc projections (o10%) previously examined in age-matched rats Ma et al, 2014). Silent synapses are generally abundant in the developing brain, contributing to active plastic changes at synapses and circuits, but decline to very low levels after development (Durand et al, 1996;Kerchner and Nicoll, 2008).…”
Section: Altered Properties Of Pvt-to-nac Synapses 1-2 D After Cocainsupporting
confidence: 47%
See 1 more Smart Citation
“…A minimal stimulation assay (Isaac et al, 1995;Liao et al, 1995;Huang et al, 2009) revealed that silent synapse levels were significantly increased within this projection (Figure 2a-c; t(25) = 2.69, po0.05, saline 21.27 ± 8.08%, cocaine 47.03 ± 5.60%). We also noted that the basal (saline) levels of silent synapses (~20%) appear to be higher in this projection than other NAc projections (o10%) previously examined in age-matched rats Ma et al, 2014). Silent synapses are generally abundant in the developing brain, contributing to active plastic changes at synapses and circuits, but decline to very low levels after development (Durand et al, 1996;Kerchner and Nicoll, 2008).…”
Section: Altered Properties Of Pvt-to-nac Synapses 1-2 D After Cocainsupporting
confidence: 47%
“…The new spines are thought to be nascent synapses, generated initially as AMPAR-silent synapses after cocaine exposure and mature into AMPAR-present synapses after cocaine withdrawal to remodel the NAc circuits (Huang et al, 2009;Lee and Dong, 2011;Huang et al, 2013;Dong and Nestler, 2014). This notion has been further examined in two limbic projections to the NAc shell, the prefrontal cortical and amygdala projections, in which silent synapses are generated after cocaine self-administration, and a portion of them unsilences to become fully functional synapses by recruiting CP-AMPARs Ma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the PFC, cocaine/retrieval rats exhibited slightly greater proteasome activity regardless of test day, perhaps reflecting the PFC's major role in regulating cocaine seeking across experimental models (Kalivas and Volkow, 2005). However, projections originating from different PFC subregions undergo distinct adaptations during withdrawal that can both promote and oppose incubation of craving (Koya et al, 2009;Ben-Shahar et al, 2013;Ma et al, 2014). Therefore, future studies should measure UPS activity in PFC subregions.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the nucleus accumbens (NAc) because the expression of 'incubated' craving depends upon synaptic plasticity in this region (Conrad et al, 2008;Loweth et al, 2014). We also studied other regions-amygdala, prefrontal cortex (PFC) and dorsolateral striatum (DLS) -implicated in cue-induced cocaine seeking after withdrawal (Grimm et al, 2003;Fuchs et al, 2006;Lu et al, 2005aLu et al, , b, 2007See et al, 2007;Koya et al, 2009;Pacchioni et al, 2011;Lee et al, 2013;Ma et al, 2014;Pascoli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While their role in dmPFC-BLA pathway remains unknown, silent synapses are formed in the nucleus accumbens of rats during cocaine self-administration, and are involved in cocaine-induced locomotor sensitization and cocaine craving by allowing incorporation of AMPAR (Brown et al, 2011;Lee et al, 2013;Ma et al, 2014). By the same mechanism, silent synapses may render the dmPFC-BLA pathway more prone to facilitation.…”
Section: Formation and Role Of Silent Synapsesmentioning
confidence: 99%